Global imbalances, Bretton Woods II, and Euroland's role in all this - Jörg Bibow (Levy Economics Institute of Bard College, 2006)
Approaching the issue of mounting global imbalances from the perspective of the "Bretton Woods II hypothesis," this paper argues that the popular preoccupation with China's supposed export-led development strategy is misplaced. It also suggests, similar to Japan's depression, subdued growth in Euroland for most of the time since the Maastricht Treaty has been of first-order importance in these developments. Germany is identified as being at the heart of the European trouble. Globally, there is an ongoing clash between two approches to macroeconomic policy making: a highly dogmatic German approach, and a very pragmatic Anglo-Saxon one. The low levels of interest at which global demand imbalances have been smoothed out financially reflect deficient global demand in an environment of vast supply-side opportunities. After contributing greatly to the build-up of imbalances, Euroland is unlikely to play any constructive part in their unwinding. Hampered by an exchange-rate policy vacuum, a small-country mindset, and soaring intra-area imbalances, Euroland is also illpositioned to cope with fading external growth stimuli.
Keywords: E63; F02; F32; F43; N10; 330; Global Imbalances; Revised Bretton Woods; EMU; Divergences; Export-led Growth; Reserve Currency